PENGUATAN PEMBERDAYAAN EKONOMI KREATIF AGUNG HANDYCRAFT DESA KLEPU KECAMATAN CEPER KABUPATEN KLATEN - Nur Kholis; Hestin Mutmainah; Ida Ayu Kade Rachmawati Kusasih (ABDI KAMI: Jurnal Pengabdian Kepada Masyarakat, 2021)
Covid-19 has a big impact on all groups, from the government to MSMEs. The smaller the opportunity to work, eventually many people have to rethink to pay for their lives. During this time of pandemic, home businesses are growing rapidly, one of which is Mr. Agung Santoso who is a Handycraft craftsman. n implementing the Tri Dharma and having a vision and mission, Surakarta's high school of economics always provides assistance to MSME craftsmen around Solo Raya in improving the creative economy. Introduction to entrepreneurship, e-marketing and introduction to management and finance which are the main targets in the development of the Agung Handycraft business.